Hubungan Kegiatan Ekstrakurikuler Pendidikan Kepramukaan dengan Kemandirian Siswa Kelas IV dan Kelas V Sekolah Dasar Negeri 5 Kota Bengkulu - Mike Wahyu Fadma; Lukman Lukman; Resnani Resnani (JURIDIKDAS, 2019)
This study aims to determine the relationship of extracurricular activities scouting education (X) with the independence of students (Y) class IV and class V As Basic State 5 Bengkulu City. This type of research is quantitative research. The population of this study amounted to 286 students. The sample in this research is 72 students with random sampling sampling technique. Data collection techniques used questionnaires. The research instrument was tested using validity and reliability. While prerequisite analysis test by using normality test and homogeneity test. Data analysis technique is done by using "Product Moment Correlation" formula. This technique is used to determine the significance of independent variable relation and dependent variable by rhitung count with rtabel with 5% significant level. Based on the results of data analysis obtained rhitung = 0.94> rtabel = 0.235 which means there is a relationship of extracurricular activity scouting education with independence with a very strong interpretation. Furthermore, the results of significance test obtained thitung 23.14 ? ttabel = 1.671 which means there is a significant relationship between variables, with contribution of 88.36% between extracurricular activities scouting education with independence of students in grade IV and class V As Basic State 5 Bengkulu City . Based on this, it can be concluded that Ha accepted, where there is a relationship of extracurricular activity of scouting education with the independence of students in grade IV and class V State Elementary School 5 Kota Bengkulu.